PENGARUH KOMITMEN ORGANISASIONAL, DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Agus Basuki, 08.05.51.0015; Indriyaningrum, Kis (Students Journal of Economic and Management, 2013)
This study is a study that examined the effect of organizational commitment of labor discipline on the performance of employee motivation. Formulation of the problem in this study was to determine the effect of organizational commitment, work discipline, work motivation of employees working on the performance of either partially or simultaneously. Research on the organizational commitment variable (X1) labor discipline (X2) and motivation (X3) on the performance of the employee (Y) in PT Citra Nusa Insan Cemerlang Semarang. The sample in this study were employees of PT. Citra Nusa Insan Cemerlang Semarang. In the method of this study using a census method in which all members of the population sampled in this study. Respondents in this study amounted to 50 respondents and data collection method using a questionnaire (questionnaire) or primary data that is by asking questions on the questionnaire and then answered by the respondents by providing a cross to choose an answer. Analysis of data using qualitative and quantitative analyzes covering validity, reliability test regression hypothesis test that includes a t test and f test and coefficient of determination. Based on the data analysis can be concluded testing of the hypothesis is partially positive and significant relationship between organizational commitment to employee performance. There is a positive but not significant between labor discipline on the performance of employees. The influence of positive but not significant between the motivation to employee performance. Testing coefficient of determination obtained figures adjusted R Square of 0.910. This means 91% can be explained by the variables of organizational commitment, discipline and motivation to work together on employee performance. While the remaining 9% is explained by reasons other causes beyond the studied variables.Key words: Organizational Commitment, Work Discipline, Work Motivation and Employee Performance.